The Implementation of Code of Conduct for Members of Police as Accurators of Murder - Julizar Bimo Perdana Suka; Bambang Tri Bawono; Andri Winjaya Laksana (Universitas Islam Sultan Agung, 2022)
The police are figures and protectors of the community and also as law enforcement officers have committed a crime that is burdensome and disturbing to the community, namely eliminating a person's life through a planning process that contains elements of violating Article 340 of the Criminal Code for his actions that are declared unfit to carry out the police profession in accordance with the Decree National Police Chief KEP/23VII/2003 concerning the Code of Ethics for the Indonesian National Police. The purpose of the study 1) To find out and examine the application of the code of ethics for members of the Police 2) To find out and analyze the strategies taken by the Police to build its image in tackling criminal acts committed by unscrupulous members of the Police. This research method was sociological juridical which a legal research using secondary data as initial data, which was then followed by primary data in the field. The results of this study conclude that: 1) The application of the Code of Ethics for members of the Police that results in a criminal act will be processed first in a disciplinary hearing due to a dead line or time limit for the implementation of a disciplinary hearing, which is a maximum of 30 (thirty) days as in Article 19 Decree of the National Police Chief No. Pol Kep/44/IX/2004. After the implementation of the disciplinary hearing, a trial will be held within the scope of the general court in accordance with Article 2 of PP NO. 3 of 2003 concerning the Implementation of Technical Institutional General Courts for Members of the Indonesian National Police. 2) The strategy that needs to be taken by the Police to build its image in tackling criminal acts committed by unscrupulous members of the Police is that the Police are able to create familial conditions in providing services to the community and are more responsive.